2010
DOI: 10.1261/rna.2136010
|View full text |Cite
|
Sign up to set email alerts
|

RNase-assisted RNA chromatography

Abstract: RNA chromatography combined with mass spectrometry represents a widely used experimental approach to identify RNA-binding proteins that recognize specific RNA targets. An important drawback of most of these protocols is the high background due to direct or indirect nonspecific binding of cellular proteins to the beads. In many cases this can hamper the detection of individual proteins due to their low levels and/or comigration with contaminating proteins. Increasing the salt concentration during washing steps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 37 publications
(36 reference statements)
0
50
0
Order By: Relevance
“…RNAse assisted chromatography was performed as described elsewhere 27 . In brief, HTT-CAG-repeat-motifs were PCR amplified, treated with proteinase K and purified by phenol-chloroform extraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNAse assisted chromatography was performed as described elsewhere 27 . In brief, HTT-CAG-repeat-motifs were PCR amplified, treated with proteinase K and purified by phenol-chloroform extraction.…”
Section: Methodsmentioning
confidence: 99%
“…MID1 dependency of the binding of S6K and PP2Ac to HTT mRNAs with expanded CAG repeats was tested in an RNAse assisted chromatography 27 in cells with and without MID1 knockdown. Equal amounts of in vitro transcribed HTT-exon1-mRNA with either 20 or 51 CAG repeats were incubated with cell lysates that were either transfected with non-silencing control or MID1-specific short interfering RNA (siRNA) oligonucleotides.…”
Section: Mid1mentioning
confidence: 99%
“…To directly identify factors interacting with the region of the RNA comprising SNP rs3736234 and adjacent sequences, we used an efficient RNAse-assisted RNA chromatography protocol (Michlewski and Cáceres 2010) followed by identification of associated proteins by mass spectrometry. RNA pull-downs were carried out using RNA oligonucleotides corresponding to 31 nucleotides of intron 4 centered around rs3736234, in the Low-and High-Risk versions ( Table S3).…”
Section: Biochemical Identification Of Regulatory Factors Associated mentioning
confidence: 99%
“…RNAse-assisted RNA chromatography and mass spectrometry analysis RNA pull-down assay were carried out as described by Michlewski and Cáceres (2010). Sodium-m-periodate and Adipic acid dehydrazide agarose beads were purchased from Sigma-Aldrich, and A/T1 ribonuclease cocktail (Ambion) was used for RNAse-assisted digestion of RNA-protein complexes formed after incubation of the beads with HeLa or HMVEC Nuclear Extracts.…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…The RNA pulldown procedure was developed using in vitro transcribed ARiBo-tagged stem-loops present in the immature forms of miRNAs (miRNA stem-loops) to capture RNA-associating proteins from whole cell extracts (WCEs). Stem-loops derived from the precursors of let-7a-1 and let-7g were used (Bussing et al 2008;Roush and Slack 2008;Viswanathan and Daley 2010;Thornton and Gregory 2012;Nguyen and Zhu 2015;Rehfeld et al 2015), since several proteomic studies have been reported for these RNAs (Heo et al 2008(Heo et al , 2009Michlewski et al 2008;Viswanathan et al 2008;Michlewski and Caceres 2010;Chang et al 2013;Lee et al 2013). In addition, let-7a-1 and let-7g are two of the 12 human let-7 miRNAs that play important roles in mammalian development, metabolism, and cancer (Bussing et al 2008;Roush and Slack 2008;Viswanathan and Daley 2010;Thornton and Gregory 2012;Nguyen and Zhu 2015;Rehfeld et al 2015), and there is still significant interest in identifying proteins that control biogenesis of these miRNAs though interactions with the stem-loop structures present in their immature forms.…”
Section: Introductionmentioning
confidence: 99%